K. Sirvydo „Punktų sakymų” I dalies tarminės ypatybės ir jų santykis su dabartinėmis rytų aukštaičių tarmėmis - Markevičius, Valdimantas (Baltistica, 2002)
DIALECTAL PECULIARITIES OF ‘PUNKTAI SAKYMŲ’ BY KONSTANTINAS SIRVYDAS IN RELATION WITH THE CONTEMPORARY EAST AUKŠTAITISH DIALEСТDespite the fact that the original language of ‘Punktai sakymų’ (Polish ‘Pvnkty Kazan’; sermons) by Konstantinas Sirvydas has been edited, the žadininkai and žalininkai features typical of the author’s native dialect can often be noticed. The language typical of Dabužiai and Griežionėliai settlements supposed to be Sirvydas’ native place is presently devoid of the žadininkai feature. The aforementioned villages belong to the territory of the present Anykštėnai subdialect, which is distinguished by the rotininkai feature (rɔ̀.tαi instead of ra̾˙tαi). Yet this feature is absent in ‘Punktai sakymų’. It is possible that at least the outskirts of the Anykštėnai subdialect had no rotininkai feature during the lifetime of Sirvydas. Out of all the contemporary East Aukštaitish dialects, the Širvintiškiai subdialect is the closest to the one used in the writings by Sirvydas (both the language varieties are characterised by the presence of the žalininkai feature, the absence of the rotininkai feature and the distinction of the short vowels a, e, i, u in word endings). There are two substantial features typical of the phonetics used by Sirvydas as opposed to the contemporary Širvintiškiai subdialect: 1. Presence of the žadininkai feature. The contemporary subdialect of Širvintiškiai has no žadininkai feature (the pronunciation is žõ˙dis, and not žã˙dis), but there are numerous cases of the occurrence of this feature in Ukmergė court witness books of 1669. 2. Retention of non-monophthongised diphthongs uo, ie in unstressed positions. Sirvydas’ language peculiarities give us a clue that in the 17th century both the Širvintiškiai and Anykštėnai subdialects might still have had the žadininkai feature, and there was still no monophthongisation of unstressed diphthongs uo and ie in either of them.The contemporary Uteniškiai subdialect is supposed to have lost of the žadininkai feature, but recent audio recordings still indicate cases of its occurrence in the surroundings of Užpaliai, Duokiškis and other villages. It is still easy to find speakers of the Anykštėnai and Vilniškiai subdialects who have this feature.A comparison of facts allows one to conclude that speakers of the Uteniškiai and Vilniškiai subdialects have lengthened the short vowels a and e and made them half-long (tæ̾.pα‘smears’, la̾.šα ‘drips’), while the Širvintiškiai and Panevėžiškiai subdialect speakers have lengthened them to the long vowels (tæ̾.pα, la̾.šα). Uteniškiai and Vilniškiai subdialect speakers retained the žadininkai feature for a very long period, some of them up to the present. Making a and e long vowels would have resulted in the dephonologisation of ā, ē and a, e; i.e., the word rodo ‘shows’ would have totally coincided with the word rado ‘found’ (both of which would then be *ra̾˙da.), while mėto ‘throws’ would coincide completely with meto ‘season’s’ (*mæ̾˙ta.). The Širvintiškiai and Panevėžiškiai subdialects lost the žadininkai feature much earlier (*ā > o, *ē> ė). Thus, there was no danger of dephonologisation of the above-mentioned vowels.
Keywords: senieji raštai; dialektologija; K. Sirvydas